Identification of African rice genotypes with early morning flowering trait to avoid heat stress - Vimal, S.; Kora, O.K.; Koichi, F.; Venuprasad, R. (Cambridge University Press, 2024)
Early morning flowering (EMF) is a desirable trait in rice to avoid heat stress as temperatures in early morning hours are low compared to afternoon and flowering is the most sensitive stage to heat exposure. Cultivated rice accessions including both Oryza glaberrima and O. sativa were phenotyped for an EMF trait in 2016–2018 in two locations viz. Cotonou in Benin Republic and Ibadan in Nigeria. The initial screening was done in Cotonou in three phases in 2016 dry season, 2017 wet season and 2017 dry season, respectively. The 2093 accessions used in initial screening were subdivided into three groups based on flowering duration ensuring that each accession was grown under conditions which were best suited to their flowering duration. Further screening was done in Ibadan in 2018 dry season and 2018 wet season. Out of 2093 accessions taken in the initial screening only 1754 accessions germinated out of which only 64 accessions exhibited EMF phenotype consistently across the cultivated years, seasons and locations. Among the 64 accessions exhibiting EMF phenotype, 15 accessions also showed an early peak in spikelet opening time (EPSOT) trait, more than 80% flowering before 09:00 h. We conclude that 15 O. glaberrima accessions identified possessing both the EMF and EPSOT traits are suitable donors for use in breeding for heat escape in rice.